Effect of Storage Media on Fracture Resistance of Reattached Tooth Fragments - Poonia, Suman; Katewa, Akanksha; Soni, Pawan; Khairwa, Monika kumari; Buri, Mahendra; kularia, vishvas (Journal of Neonatal Surgery, 2025)
Background: The present study was planned to compare the fracture resistance of fractured incisor tooth fragments stored in four storage media namely, dry air, milk, normal saline or egg white which were eventually reattached using nanohybrid flowable composite. Material and methods: Forty- eight freshly extracted maxillary incisor were divided in to four groups.Teeth were then sectioned and fragments were stored in dry air (Group A),milk (Group B),Normal saline (Group C), and Egg white (Group D).The fragments were reattached using Nanohybrid flowable composite and tested on the Universal testing machine.Stastical analysis was performed using one way analysis of variance and post hoc Tukey's test. Results: Post hoc Tukey's test was performed for group wise comparison that showed no statistically significant difference in fracture resistance values between Group A and Group D (p=0.61, p> 0.005); Group B and Group D ( p=0.25, p> 0.005); Group C and Group A (p=0.66, p>0.005); Group D and Group A (p=0.61, p> 0.005). ANOVA indicated no significant difference between Group A, Group B, Group C, Group D. Conclusion: This study shows that the use of storage media for the hydration of the fractured tooth fragment does affect its fracture resistance. Within the limitations of this study, it is concluded that Normal saline offers highest fracture resistance for 2 h. followed by Milk, with least being in Egg white.